El anarquismo de Spinoza. La fundación de una ontología emancipadora - Bonilla Pereira, Jason Andrey (2020)
The philosophy of Spinoza is pierced by a savagery that brings the opportunity to conceived an emancipation from the organization of the infinite, in its articulation with the density and multiplicity that falls in the spontaneous activity of the subject. This article pretends to show how to make possible an ontological project from an anarchist condition that questions hierarchies shielded by transcendent norms.